Development of an integrated laboratory information management system of the maize mapping project - Sánchez Villeda, H.; Schroeder, S.; McMullen, M.; Havermann, S.; Davis, G.; Vroh Bi, Irie; Cone, K.; Duru, N.; Yim, Y.S.; Gardiner, J.; Polacco, M.; Fang, Z.; et al. (Oxford University Press, 2003)
Motivation: The development of an integrated genetic and physical map for the maize genome involves the generation of an enormous amount of data. Managing this data requires a system to aid in genotype scoring for different types of markers coming from both local and remote users. In addition, researchers need an efficient way to interact with genetic mapping software and with data files from automated DNA sequencing. They also need ways to manage primer data for mapping and sequencing and provide views of the integrated physical and genetic map and views of genetic map comparisons.Results: The MMP-LIMS system has been used successfully in a high-throughput mapping environment. The genotypes from 957 SSR, 1023 RFLP, 189 SNP, and 177 InDel markers have been entered and verified via MMP-LIMS. The system is flexible, and can be easily modified to manage data for other species. The software is freely available.